Design of Mechanisms to Prevent engine stalling during take off and gear shifting - Tafesh, Abdelnasser; Ghunaim, Qutaiba; Talahmeh, Hamza (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2013)
New drivers , drivers with low experience and disabled people are suffering from difficulties such as engine stalling during vehicle take off, gear shifting and choice of unsuitable gear ratio, while driving vehicle with manual gear box. To overcome these difficulties we will design assistance systems ( electronic systems and mechanical system ) to help driver to prevent engine stalling in mentioned conditions. First system: electric systems which include sensors , switches and microcontroller to overcome engine stalling due to choice of unsuitable gear ratio. Second system: mechanical system which include pneumatic – chock – absorber that will be added to clutch pedal to overcome engine stalling during vehicle take off and gear shifting.
no of pages 90, 26831, ميكانيك 17/2013 , in the store
Keywords: Mechanisms to Prevent engine stalling